Green synthesis of solanum trilobatum capped silver nanoparticle mediates high performance antimicrobial Activities - Santheraleka A/P Ramanathan (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
This research encompasses the evaluation of antimicrobial activity involving the studies on green synthesis of silver nanoparticle (AgNP) using Solanum trilobatum bark extract. The significance of S. trilobatum alone is boundless as it is recognized as medicinal herb for common health infections since ancient time. Consequently, silver metal alone has the remarkable capacity on preserving a non-infectious environment. Herein, the interest on green synthesis of AgNP using plant extract has focused for its eco-friendly and efficient method in contrast with the chemical and physical methods.